Developing A Voting System In UUM Using Mobile Technology - Almatarneh, Mohammad Nasri Abdullah (2008)
In democratic societies, voting is an important issue to reflect people opinions. This study aims to design and develop a mobile voting system for the student council in UUM, to replace the current manual voting system. The system will provide more flexibility and convenience to the students to cast there votes by saving there time and effort, and reduce the cost for the election process. The developed system shows that the objectives of the study were achieved successfully. Finally, the system is tested and the result confirms that the proposed system is capable to record a successful completion of the election process.